Who Owns This Text?: Plagiarism, Authorship, and Disciplinary Cultures - Mullin, Joan A. (Utah State University, University Libraries, 2009)
Carol Haviland, Joan Mullin, and their collaborators report on a three-year interdisciplinary interview project on the subject of plagiarism, authorship, and ""property,"" and how these are conceived across different fields. The study investigated seven different academic fields to discover disciplinary conceptions of what types of scholarly production count as ""owned."" Less a research report than a conversation, the book offers a wide range of ideas, and the chapters here will provoke discussion on scholarly practice relating to intellectual property, plagiarism, and authorship---and to how these matters are conveyed to students. Although these authors find a good deal of consensus in regard to the ethical issues of plagiarism, they document a surprising variety of practice on the subject of what ownership looks like from one discipline to another. And they discover that students are not often instructed in the conventions of their major field.